The Effect of SMEs on Social Development in Zimbabwe: A Case Study of Zimbabwe’s Home Industries (Global Journal of Management and Business Research, 2025)
This research sought to investigate the contribution of SMEs to social development Owing to the exponential increase in unemployment and retrenchments from the formal sector in Zimbabwe there is a critical absence of empirical evidence to support SMEs as viable alternatives for income generation and employment as well as general uncertainty about the contribution of the sector to the national economy This study was significant since SMEs are believed to have a role upon employment creation particularly for the less qualified people of society as well as income generation and since they are understood to have the potential to fight poverty and aid development which also helps through the generation of information for policymaking purposes The objectives of the study were therefore to detail the structure of Zimbabwe s SME sector to investigate its employment creation ability as well as to assess the average monthly incomes of the employees within this sector
Keywords: SMEs; social development; income generation; employment; contribution to national economy